Biotechnology for agroindustries - Mel, Maizirwan (2009)
Biotechnology is technology based on biology, especially when used in agriculture, food science, and medicine. United Nations Convention on Biological Diversity defines biotechnology as "Any technological application that uses biological systems, dead organisms, or derivatives thereof, to make or modify products or processes for specific use.~ Before 1971, the term, biotechnology, was primarily used within the agriculwral industries. Current uses of the term generally refer to the technologies associated with genetic engineering as well as cell and tissue cultw'e. Biotcchnology draws on the pure biological sciences (genetics, microbiology. molecular biology,biochemistry, embryology, cdl biology) and in many instances is also dependent on knowledge and methods from outside the sphere of biology (chemical engineering. information technology, biorobotics).Conversely, modem biological sciences (including even concepts such as molecular ecology) are intimately entwined and dependent on the methods developed through biotechnology and what is commonly thought of as the life sciences industry.Biotechnology has applications in four major industrial areas, including health care (medical), crop production and agriculture. non food (industrial) uses of crops and other products (e.g. biodegradable plastics, vegetable oil, bie-fuels), and environmental uses.